Investigating a role for heterotrimeric G-proteins in activating TGFβ in asthma - Middlewick, Robert James (2020)
Asthma is a chronic inflammatory disease of the airways, affecting 5.4 million people in the UK. Asthma pathology is characterised by airway hyper-responsiveness, bronchoconstriction, and airway remodelling. Airway remodelling is particularly prominent in severe asthma and describes structural changes within the airways including, ASM hyperplasia and hypertrophy, subepithelial fibrosis, mucus gland hyperplasia, and angiogenesis. The pleiotropic cytokine TGFβ is plays a central role in the development of all airway remodelling characteristics and is found to have increased activation in asthmatics versus non-asthmatics. Previous studies in ASM cells has shown that the integrin αvβ5 and the actin cytoskeleton is essential for TGFβ activation. Moreover, the heterotrimeric G-proteins Gαq/11 have been implicated in TGFβ activation in murine embryonic fibroblasts and epithelial cells. However, the class of heterotrimeric G-protein required for TGFβ activation in ASM has not been established. The hypothesis of this thesis is that the heterotrimeric G-proteins Gαq/11 are required for TGFβ activation in ASM cells.